Reimagining Teacher Education through Design Thinking Principles: Curriculum in the Key of Life - Latremouille, Jodi; Grant, Kimberley; Kalu, Frances; Dodsworth, Dianne; Knowlton Cockett, Polly; Mitchell-Pellett, Mary-Ann; Paul, Jim (Journal of the Canadian Association for Curriculum Studies, 2015)
Inspired by Arendt’s (2009) “task of renewing a common world” (p. 193), a team of ten instructors took on the challenge of reimagining a teacher preparation course entitled Curriculum II - Arts & Humanities. Through the dominant discourses of management, accountability and technique-driven preparation, the act of teaching is interpreted as a “service rendered” (Pinar, 2012, p. 36), measured “objectively” by demonstrable deliverables and pre-determined outcomes. Our team provoked these discourses by asserting that human beings are inherently attuned to deeper learning through wonderment, interpretation, ideation and experimentation (Whitehead, 1929). The principles of design thinking – a problem-based process which, through curiosity, empathy and interdisciplinary thinking, generates playful and collaborative creative experimentation – offered a space within which to open up deeper educational conversations with pre-service teachers. Invoking the metaphor of a choral performance, this series of miniature musical movements “in the key of life” express the challenging, enlivening and multivocal nature of curriculum and pedagogy enacted through Design Thinking principles. From contemplating the power of self-reflection and collective action, to meeting challenges and resistance with courage, to listening with heart to people and places, and to responding with joy and hope in the face of our place and circumstances, each individual movement gives voice to the echoes that linger long after the official coursework is complete. Together, these voices join together in a chorus of authentic and responsive curriculum renewal.